The measurement tool to evaluate the sustainability of Geran Khas Prihatin (GKP) To Post Covid19 Recipients’ in Retaining SME’S Business / Nor Faezah Mohamad Razi ... [et al.] - Mohamad Razi, Nor Faezah; Sarkam, Nor Aslily; Mohammad, Nor Hazlina; Nasarudin, Nur Hasni; Ahmad Junid, Rosida (2021)
SMEs face a variety of challenges. Due to the pandemic, SME business owners have had to modify their business models to adapt to this situation. Some of them succeeded, but some of them had to close their business. The organization must be able to withstand adversities and changes to be resilient in this pandemic. To be sustainable, the organization must meet the needs of the present without compromising the future. Multiple changes in the Government's Movement Control Operation (MOC) to stop the transmission of Covid 19 to minimize the economic sector have indirectly affected SME activities. According to Malaysian economic research (MIER), 95% of SMEs will suffer a decline in sales. To ensure the resilience of SMEs in Malaysia, the Government has launched one of the initiatives by offering a special grant known as Geran Khas Prihatin (GKP) for every micro- enterprise that will benefit almost 700,000 micro-enterprises across the country. It is believed to provide a survival line for Malaysian SMEs to expand or strengthen their financial situation in the post-Covid 19 periods. However, it is necessary to study and investigate how this initiative can help support and develop SMEs' enterprises. Perhaps the GKP subsidy is sufficient to permit SMEs and all beneficiaries to effectively used the grant to grow their business. Still, there is not enough study conducted to evaluate the tools for measuring the efficiency of GKP. Consequently, we will know that the GKP initiative's implementation meets the grant's objective or vice versa.